Estimation of Metabolisable Energy Values of Diets Containing Glycerin or Corn Starch to be used in Early Nutrition of Broiler Chicks (Journal of Hama University, 2019)
A digestibility experiment was carried out using 45 unsexed chicks of a commercial broiler breed taken from a hatchery nearby the farm of the experiment. When the chicks started to hatch, the chicks were collected without the need to complete the operation of hatching to ensure that the hatching chicks were hatched at the same time. The chicks were distributed into three groups of each group divid into 3 sub-groups each sub group contains 5 chicks. The chicks were fed different diets as follows:The chicks of the 1st group were given the broiler diet directly after hatching. The chicks of 2nd group were given the broiler diet Contain 5% Glycerin directly after hatching. The chicks of the 3rd group were given the broiler diet Contain 5% Corn starch directly after hatching. The three groups were fed until the end of the experiment 7 days old are free.The results show using glycerin 5% in diets increase Apparent Metabolisable Energy and True Metabolisable Energy in this diet with significant differences (P≤0.05) compare with control group. The results show using Corn starch no significant differences (P≤0.05) with control group.The results show no significant differences in the average live weight of the groups studied during the first three days of life.